Enhanced and cross-reactive in vitro memory B cell response against Epstein-Barr virus nuclear antigen 1 in multiple sclerosis - Marti, Zoe; Ruder, Josefine; Thomas, Olivia G.; Bronge, Mattias; De La Parra Soto, Lorenzo; Grönlund, Hans; Olsson, Tomas; Martin, Roland (Frontiers in Immunology, 2024)
Multiple sclerosis (MS) is a prototypical autoimmune disease of the central nervous system (CNS). In addition to CD4+ T cells, memory B cells are now recognized as a critical cell type in the disease. This is underlined by the fact that the best-characterized environmental risk factor for MS is the Epstein-Barr virus (EBV), which can infect and persist in memory B cells throughout life. Several studies have identified changes in anti-EBV immunity in patients with MS. Examples include elevated titers of anti-EBV nuclear antigen 1 (EBNA1) antibodies, interactions of these with the MS-associated HLA-DR15 haplotype, and molecular mimicry with MS autoantigens like myelin basic protein (MBP), anoctamin-2 (ANO2), glial cell adhesion molecule (GlialCAM), and alpha-crystallin B (CRYAB). In this study, we employ a simple in vitro assay to examine the memory B cell antibody repertoire in MS patients and healthy controls. We replicate previous serological data from MS patients demonstrating an increased secretion of anti-EBNA1380-641 IgG in cell culture supernatants, as well as a positive correlation of these levels with autoantibodies against GlialCAM262-416 and ANO21-275. For EBNA1380-641 and ANO21-275, we provide additional evidence suggesting antibody cross-reactivity between the two targets. Further, we show that two efficacious MS treatments – natalizumab (NAT) and autologous hematopoietic stem cell transplantation (aHSCT) – are associated with distinct changes in the EBNA1-directed B cell response and that these alterations can be attributed to the unique mechanisms of action of these therapies. Using an in vitro system, our study confirms MS-associated changes in the anti-EBNA1 memory B cell response, EBNA1380-641 antibody cross-reactivity with ANO21-275, and reveals treatment-associated changes in the immunoglobulin repertoire in MS.